Evaluation of electromagnetic field levels generated from mobile communication stations near the University of Karbala - Alali, Rasha (Technium BioChemMed, 2025)
This study systematically measured the density of power levels of electromagnetic fields (EMFs) emitted by mobile base station towers operating in the 900 MHz, 1800 MHz, and 2100 MHz frequency bands in Karbala, Iraq. Using a German-designed Narda SRM 3006 micro spectrum analyzer, we assessed exposure levels in multiple directions around the University of Karbala. We also used GIS software, ArcGIS 10.7.1, to map nearby towers and emission directions. By comparing the measured power densities with national and international safety standards—including those set by the Iraqi Ministry of Health and Environment, the International Commission on Non-Ionizing Radiation Protection (ICNIRP), the Federal Communications Commission (FCC), and the Institute of Electrical and Electronics Engineers (IEEE)—we found that all recorded levels were within permissible exposure limits. Notably, the highest average measured power density was 358.2 nW/cm² at the 2100 MHz frequency band. These results confirm that telecommunications tower emissions in the studied areas comply with global radiation safety standards, providing valuable insights into public health safety from electromagnetic exposure. Our research establishes important foundations for monitoring electromagnetic fields in urban environments, supporting efforts to implement safe radiation limits and guiding future policy decisions.